Answer:
x = 2 , y = 1
Explanation:
Solve the following system:
{y = 3 x - 5 | (equation 1)
3 y + 6 x = 15 | (equation 2)
Express the system in standard form:
{-(3 x) + y = -5 | (equation 1)
6 x + 3 y = 15 | (equation 2)
Swap equation 1 with equation 2:
{6 x + 3 y = 15 | (equation 1)
-(3 x) + y = -5 | (equation 2)
Add 1/2 × (equation 1) to equation 2:
{6 x + 3 y = 15 | (equation 1)
0 x+(5 y)/2 = 5/2 | (equation 2)
Divide equation 1 by 3:
{2 x + y = 5 | (equation 1)
0 x+(5 y)/2 = 5/2 | (equation 2)
Multiply equation 2 by 2/5:
{2 x + y = 5 | (equation 1)
0 x+y = 1 | (equation 2)
Subtract equation 2 from equation 1:
{2 x+0 y = 4 | (equation 1)
0 x+y = 1 | (equation 2)
Divide equation 1 by 2:
{x+0 y = 2 | (equation 1)
0 x+y = 1 | (equation 2)
Collect results:
Answer: {x = 2 , y = 1